Efficacy and safety of Runzao Zhiyang capsule for chronic urticaria: a systematic review and meta-analysis of randomized controlled trials - Zhang, Jian-Feng; Wang, Ying-Dong; Lin, Peng; Li, Jun-Chen; Guo, Chen-Qi; Zhai, Jing-Bo; Zhang, Yu (Frontiers in Pharmacology, 2023)
Background: Chronic urticaria (CU) is a commonly seen skin disorder featured by recurring wheals, with or without angioedema, lasting for at least 6 weeks. Runzao Zhiyang capsule (RZC) has been widely applied to treat patients with CU. This study is aimed at systematically evaluating the efficacy and safety of RZC in treating CU. Materials and Methods: Randomized controlled trials (RCTs) of RZC on treating CU from Chinese and English databases were searched. Data were collected by two independent researchers. The Cochrane Collaboration tool was adopted for evaluating the risk of bias. The meta-analysis was performed with Review Manager 5.3 software. Sensitivity analysis and publication bias assessment were conducted by Stata 14.0 software. Results: Totally 27 studies were included in the analysis, involving 2703 patients. The pooled results showed that compared with second-generation H1-antihistamines (sgAHs) therapy alone, RZC combined with sgAHs is more effective in improving the total effective rate (RR=1.32, 95% CI: 1.25 to 1.39, P < 0.00001), the quality of life measured by Dermatology Life Quality Index (DLQI) (MD=-2.63,95% CI: -3.68 to -1.58, P < 0.00001) and the serum IFN-γ level (SMD=3.10, 95% CI: 1.58 to 4.62, P<0.0001), and reducing the recurrence rate (RR=0.39, 95% CI:0.27 to 0.55, P<0.00001), the serum total IgE level (SMD=-2.44, 95% CI: -3.51 to -1.38, P<0.00001), the serum IL-4 level (SMD=-2.96, 95% CI: -4.10 to -1.83, P<0.00001), and the incidence of adverse events including dizziness, fatigue, dry mouth, and constipation (RR=0.53, 95% CI: 0.33 to 0.85, P=0.009; RR=0.46, 95% CI: 0.26 to 0.84, P=0.01; RR=0.57, 95% CI: 0.34 to 0.95, P=0.03; RR=0.24, 95% CI: 0.07 to 0.85, P=0.03). Conclusion: The current evidence indicates that RZC may be an efficient therapeutic regimen in patients with CU. Nevertheless, owing to the suboptimal quality of the included studies, more large-scale, well-designed RCTs are required to verify the obtained findings.